Use of multispectral remote sensing data to map magnetite bodies in the Bushveld Complex, South Africa : a case study of Roossenekal, Limpopo - Roberts, R.J. (James) (University of Pretoria, 2020)
Dissertation (MSc)--University of Pretoria, 2019.